Silicon isotope fractionation during abiotic silica precipitation at low temperatures: Inferences from flow-through experiments - Geilert, Sonja; Vroon, Pieter Z.; Roerdink, Desiree L.; Van Cappellen, Philippe; van Bergen, Manfred J. (Geochimica et cosmochimica acta, 2014)
Silicon isotopes have considerable potential as proxy for (near-) surface processes and environmental conditions. However, unambiguous interpretations of isotope signatures in natural silica deposits are often hampered by a lack of independent quantitative information on isotopic fractionations operating under the environmental conditions of interest. We performed seeded silica precipitation experiments using flow-through reactors in the 10-60 degree C temperature range to alleviate this problem. The principal objective was to quantify the silicon isotope fractionations during controlled precipitation of amorphous silica from a flowing aqueous solution. The experiments were designed to simulate silica deposition induced by a temperature drop, with particular relevance for (near-) surface hydrothermal systems associated with steep temperature gradients. Monitored differences in silicon isotope ratios ( super(30)Si/ super(28)Si and super(29)Si/ super(28)Si) between input and output solutions demonstrated a systematic sequence in behavior. During an initial time interval, that is, before the reaction system reached steady state, the observed isotope shifts were influenced by dissolution of the seed material, the saturation state of the solution and the specific surface area of the seeds. After reaching steady state, the selective incorporation of silicon isotopes by the solid phase exhibited an explicit temperature dependency: the lighter isotopes were preferentially incorporated, and apparent fractionation magnitudes increased with decreasing temperature. Calculated magnitudes of silicon isotope fractionations between precipitated and dissolved silica ( Delta super(30)Si = delta super(30)Si sub(precipitate (calculated)) - delta super(30)Si sub(input solution)) were -2.1ppt at 10 degree C, -1.2ppt at 20 degree C, -1.0ppt at 30 degree C, -0.5ppt at 40 degree C, 0.1ppt at 50 degree C, and 0.2ppt at 60 degree C (s.d. [el] 0.6ppt, based on replicate experiments). Hence, fractionation was nearly insignificant at temperatures >=50 degree C. Apart from this relationship with temperature, our results indicate that the effective Si isotope fractionation during precipitation from a solution is subject to changes in the saturation state, reactive surface area and flow regime. We therefore infer that, to a significant extent, solid-fluid fractionation in natural (near-) surface environments is system dependent.